The social organisation of migrant smugglers in Turkey: roles and functions - Demir, Oguzhan Omer (European journal on criminal policy and research, 2017)
Thousands of irregular migrants and refugees are transported from conflict areas and/or underdeveloped countries to wealthy Western states. These transfers are usually facilitated and arranged by migrant smuggling organisations. This paper reflects part of a comprehensive research project on irregular migration and migrant smuggling in Turkey and examines the structure and networks of smugglers operating in Turkey. Based on face-to-face interviews with smugglers (N = 54), it aims to shed light on migrant smugglers, smuggling structures and their organisations in Turkey. The findings suggest that the migrant smuggling business is composed of networks established at the local, national and international levels. These are structured on an ad hoc basis and are often adaptable to any changes and opportunities that may arise.